2016
DOI: 10.1177/0022034516679136
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Satellite Cells Form Small Myotubes In Vitro

Abstract: Although palatal muscle reconstruction in patients with cleft palate takes place during early childhood, normal speech development is often not achieved. We hypothesized that the intrinsic properties of head satellite cells (SCs) and the young age of these patients contribute to the poor muscle regeneration after surgery. First, we studied the fiber type distribution and the expression of SC markers in ex vivo muscle tissue from head (branchiomeric) and limb (somite-derived) muscles from neonatal (2-wk-old) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…At ten-week age, SCs proportion in LVP muscle were much more than 1%, yet remaining well below 1% in MAS muscle and TA muscle. Heterogeneities in SCs proportion among muscles of different embryonic origins or different ages were also reported by other studies 11 , 26 , 27 . It has been proved by Carvajal Monroy that rat LVP muscle and MAS muscle contained more SCs than limb muscle 27 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…At ten-week age, SCs proportion in LVP muscle were much more than 1%, yet remaining well below 1% in MAS muscle and TA muscle. Heterogeneities in SCs proportion among muscles of different embryonic origins or different ages were also reported by other studies 11 , 26 , 27 . It has been proved by Carvajal Monroy that rat LVP muscle and MAS muscle contained more SCs than limb muscle 27 .…”
Section: Discussionsupporting
confidence: 82%
“…Heterogeneities in SCs proportion among muscles of different embryonic origins or different ages were also reported by other studies 11 , 26 , 27 . It has been proved by Carvajal Monroy that rat LVP muscle and MAS muscle contained more SCs than limb muscle 27 . Keefe reported that the SCs density varied nearly five folds among different muscles 26 .…”
Section: Discussionsupporting
confidence: 82%
“…They express the paired box transcription factor 7 (Pax7) and are located between the sarcolemma and basal lamina surrounding a single muscle fiber. After the injury, SCs become activated and migrate to the site of injury, proliferate, and differentiate into myoD‐positive myoblasts that fuse to form new multinucleated myosin heavy chain (MyHC)‐positive myofibers or repair damaged myofibers (Figure ) . A small portion of these SCs stay quiescent to allow future regeneration cycles.…”
Section: Stem Cells Repair Wounds and Facilitate Skin And Muscle Regementioning
confidence: 99%
“…SCs from different branchiomeric muscles, however, behave in a similar way. The lower regenerative capacity of branchiomeric muscles compared to limb muscle may impair muscle healing after cleft surgery . The reduced blood supply and aberrant muscle orientation in a cleft lip may further impair the regeneration process .…”
Section: Stem Cells Repair Wounds and Facilitate Skin And Muscle Regementioning
confidence: 99%
See 1 more Smart Citation